Urban Sprawl Mapping For Sport-Based Tourism Suitability Using GIS-AHP Model - Shahazmeer, Che Dandang (2023)
Due to the increasing expansion of urban areas and the increased demand for sport-based tourism, it is necessary to choose appropriate venues for sports-related activities that take place within urban environments. In order to accomplish this goal, effective planning and decision-making tools are required. This study suggests using a Geographic Information System (GIS) in conjunction with the Analytic Hierarchy Process (AHP) when evaluating and mapping the potential for sport-based tourism activities in urban regions. The data from Geographic Information Systems (GIS) are combined with the AHP methodology in this model. This is done so that the model can predict which sites have the most potential for the expansion of sport-based tourism. The model takes into account a wide variety of characteristics, including environmental quality, accessibility, land use patterns, and transportation infrastructure, to name just a few of them. The AHP provides relative relevance ratings for each component, and the GIS makes it possible to perform geographical analysis and present the results of that study. This method provides essential information for the city planners and developers, which makes resource allocation easier and helps to enhance tourism based on sporting events. The concept that has been offered can help with a variety of things, including making cities a more desirable place to live, helping the economy, making people happy, and safeguarding the environment.